Accelerated Depreciation Allowances as a Stimulus to Investment - Goode, Richard (Quarterly Journal of Economics, 1955)
I. General discussion, normal and accelerated depreciation allowances, 192; influence on investment, 194; factors affecting influence of accelerated depreciation, 201; revenue effects, 203; comparison with reduction of tax rates, 204; accelerated depreciation as an alternative to other tax concessions in under-developed countries, 207; comparison with reduction of interest rates, 209. — II. Comparison of accelerated-depreciation methods, 211; use of the methods, 212; annual charges and their present value, 213; appraisal, 218. — III. Conclusion, 219.